PROFIL PELAJAR PANCASILA DALAM MENANAMKAN SIKAP EMPATI SISWA SEKOLAH DASAR - Hilal Dwi Cahyo; Mohamad Syarif Sumantri; Linda Zakiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Growing the empathy students is very necessary in this era as an effort to realize a superior and moral generation. This study aims to find out more about how students' empathetic attitudes are as a result of the implementation of the Pancasila Student Profile Program. The type of research used is descriptive qualitative research. Data collection techniques are based on observation, interviews, and documentation. Based on observations and interviews, it shows that teachers at SDN Kelapa Dua 03 morning, especially grade IV teachers, have applied the values in the Pancasila student profile to learning using differentiated learning strategies .The results of using this strategy in implementing the pancsila student profile in learning can be seen by the presence of students who have an increasing sense of empathy, and also show mutual cooperation.